Hyaluronan Expression on Vitrified Oocytes Before and After In Vitro Maturation (EKSPRESI HYALURONAN PADA OOSIT YANG DIVITRIFIKASI SEBELUM DAN SESUDAH MATURASI IN VITRO) - Faizah, Zakiyatul; Aswin, R. Haryanto; Lunardhi, Hamdani; Widjiati, Widjiati (Jurnal Veteriner; Vol 19 No 1 (2018), 2018)
Oocyte vitrification is a major challenge in assisted reproductive technology. Oocyte vitrification with cumulus cells provide benefits in the process of maturation and fertilization. Vitrification leads to rapid temperature changes, therefore the decreasing in temperature could damage the cells even when the morphology was normal. Vitrification of mature oocytes is common because of its low sensitiveness towards low temperatures than immature oocytes. The aim of the research was to compare the effect of vitrification before and after in vitro maturation to the expression of hyaluronan. Maturation was operated in medium TC 50 ?L in CO2 incubators for 24 hours. Vitrification started with washing oocyte in PBS basic medium supplemented with 20% serum for 1-2 minutes, then in equilibration medium PBS + 20% serum + 10% ethylene glycol for 10-14 minutes, then transferred to 20% serum + PBS + 0.5 M sucrose + 15% ethylene glycol + PROH 15% for 25-30 seconds. Thawing was processed by submerging the oocytes in the media: 1). PBS + 20% serum + 0.5 M sucrose (K1); 2) PBS + 20% serum + 0.25 M sucrose (K2); and 3).PBS + 20% serum + 0.1 M sucrose (K3). Immunocytochemical stain was performed to evaluate the hyaluronan expression. Remmele scale index (Immunoreactive score, IRS) was used to read the result. There was no differences of hyaluronan expression in oocyte and cumulus group of K1, K2 and K3 at p< 0.05, statistically. We concluded that there was no difference of hyaluronan expression on oocyte and cumulus between vitrified oocyte of pre and post in vitro maturation which indicated that oocyte could be vitrified in the immature and mature state.